The impact of a Canadian external Employee Assistance Program on mental health and workplace functioning: Findings from a prospective quasi-experimental study. (3rd July 2019) - Milot, Marc
Abstract: In this investigation, a quasi-experimental prospective evaluation employing a pretest–posttest control group design with propensity score matching estimated the causal impacts of a Canadian Employee Assistance Program (EAP) on mental health, workplace functioning, and life satisfaction. Participants ( N = 304) were employees working at different organizations across Canada. EAP users had access to up to 12 counseling hours per year. Outcomes were compared between groups of EAP ( n = 152) and non-EAP ( n = 152) users matched on numerous baseline variables including demographic, occupational, mental health, workplace functioning, and other characteristics and measures. At 6 month follow-up, EAP users had significantly reduced psychological distress, including reduced symptoms of depression and anxiety compared to non-EAP users. EAP users also had significantly reduced work presenteeism and work distress, and increased work engagement. Finally, they reported greater life satisfaction at follow-up relative to non-EAP users. The largest effect sizes of EAP counseling were observed on mental health outcomes. Mediation analyses revealed that EAP treatment effects on workplace functioning were mediated by changes in (their positive impacts on) mental health. This is the first known quasi-experimental study conducted with an external EAP, with evidence supporting a causal link between use of a Canadian assistance program and a number of positive clinical and workplace outcomes.